[TEX]\frac{x}{2}=\frac{y}{3}\Rightarrow x= \frac{2y}{3}[/TEX] (1)
[TEX]\frac{x}{2}=\frac{z}{4}\Rightarrow x=\frac{2z}{4}=\frac{z}{2} [/TEX] (2)
Từ (1)&(2) [TEX]\Rightarrow \frac{2y}{3}=\frac{z}{2}[/TEX]
[TEX]\Rightarrow 4y=3z \Rightarrow z=\frac{4y}{3}[/TEX]
Xét : [TEX]y+z-x=y+\frac{4y}{3}-\frac{2y}{3}[/TEX]
[TEX]=\frac{2y}{3}+y[/TEX]
[TEX]=\frac{2y}{3}+\frac{3y}{3}[/TEX]
[TEX]=\frac{5y}{3}[/TEX]
Xét : [TEX]x-y+z=\frac{2y}{3}-y+\frac{4y}{3}=\frac{6y}{3}-y[/TEX]
[TEX]=2y-y=y[/TEX]
Ta Có [TEX]\frac{y+z-x}{x-y+z}=\frac{\frac{5y}{3}}{y}=\frac{5}{3}[/TEX]